Impact of Moving/Exponentially Accelerated Vertical Plate on Unsteady Flow and Heat Transfer in Hybrid Nanofluids - Rajesh, Vemula; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal H. (Amer Scientific Publishers, 2023)
The main goal of this work is to explore exact analytical solutions for the transient hybrid nanofluid flow with heat transfer owing to a moving/exponentially accelerating infinite flat vertical plate with heat flux boundary conditions. Further, the uniqueness of this work is to investigate the impact of different types of hybrid nanofluids on heat transfer and unsteady flow features in the existence of thermal radiation and heat flux boundary conditions. For engineering variables like Nusselt number and skin friction coefficient, along with temperature and velocity profiles, graphs are used to reveal the results of the Laplace transform method. Increased heat transfer and friction values have been found for an exponentially accelerating plate. The findings can be utilized in heat exchangers as well as in electronics and chemical and biological reactors.
Keywords: Laplace Transform Technique; Heat Flux; Infinite Vertical Plate; Unsteady Flow; Hybrid Nanofluid